RNAi-mediated CD40-CD154 interruption promotes tolerance in autoimmune arthritis - Zheng, Xiufen (BioMed Central, 2010)
INTRODUCTION: We have previously demonstrated that ex vivo inhibition of costimulatory molecules on antigen-pulsed dendritic cells (DCs) can be useful for induction of antigen-specific immune deviation and suppression of autoimmune arthritis in the collagen induced arthritis (CIA) model. The current study evaluated a practical method of immune modulation through temporary systemic inhibition of the costimulatory molecule CD40. METHODS: Mice with collagen II (CII)-induced arthritis (CIA) were administered siRNA targeting the CD40 molecule. Therapeutic effects were evaluated by clinical symptoms, histopathology, Ag-specific T cell and B cell immune responses. RESULTS: Systemic administration of CD40-targeting siRNA can inhibit antigen-specific T cell response to collagen II, as well as prevent pathogenesis of disease in both a pre- and post-immunization manner in the CIA model. Disease amelioration was associated with suppression of Th1 cytokines, attenuation of antibody production, and upregulation of T regulatory cells. CONCLUSIONS: These studies support the feasibility of transient gene silencing at a systemic level as a mechanism of resetting autoreactive immunity.